Ultrastructural Details of Cryptosporidium parvum Development in Calf Intestine - Mª José Rosales; Teresa Arnedo; Carmen Mascaró (Memorias do Instituto Oswaldo Cruz, 1998)
Cryptosporidium parvum and C. muris appear to be different species found in calves, with different oocysts size and distribution on the gastrointestinal tract. This work presents new images of C. parvum ultrastructure in calf intestine, mainly its development in nonmicrovillous cells and the presence of microtubular structures in the membrane enveloping the macrogamonts and immature oocysts.